Fatty Acid, Essential Oil and Phenolic Compositions of Alcea pallida and Alcea apterocarpa with Antioxidant, Anticholinesterase and Antimicrobial Activities - Abdulselam Ertas (Science Faculty of Chiang Mai University, 2019)
This study was the first phytochemical and biological activity report on Alcea pallida and Alcea apterocarpa extracts. The main constituents of the essential oils were identified as arachidic acid (34.2%) for A. pallida, and hexatriacontane (25.3%) for A. apterocarpa. The main constituents of the fatty acids obtained from petroleum ether extracts of A. pallida and A. apterocarpa were identified as palmitic acid (31.2%) and oleic acid (25.6%), respectively. The phenolic compositions of the samples were determined using HPLC (LC-20 liquid chromatographic system). A. pallida and A. apterocarpa showed the same peaks which were ascorbic, caffeic, salicylic and p-hydroxybenzoic acids and quercetin, respectively. Salicylic acid showed the highest abundance. Among the eight extracts, the acetone extract of A. pallida possessed the best ABTS cation radical scavenging activity and moderate butyryl-cholinesterase activity at 200 mg/mL. The A. pallida acetone extract exhibited 53.12% inhibition in DPPH free radical scavenging activity method at 100 mg/mL concentration. The acetone extract of A. pallida showed weak antimicrobial activity against Escherichia coli, Streptococcus pyogenes, Staphylococcus aureus, Pseudomonas aeruginosa and moderate activity against Candida albicans (inhibition zone diameter 16 mm). The acetone extract of A. apterocarpa showed moderate activity against C. albicans (inhibition zone diameter 14 mm) and S. aureus (inhibition zone diameter 13 mm); weak activity against E. coli., S0 pyogenes, and P. aeruginosa.